Australia’s Private Refugee Sponsorship Program: Creating Complementary Pathways Or Privatising Humanitarianism? - Hirsch, Asher Lazarus; Hoang, Khanh; Vogl, Anthea (Refuge: Canada's Journal on Refugees, 2019)
Abstract This article provides the first history and critique of Australia’s private refugee sponsorship program, the Community Support Program (CSP). As more countries turn to community sponsorship of refugees as a means to fill the “resettlement gap,” Australia’s model provides a cautionary tale. The CSP, introduced in 2017, does not expand Australia’s overall resettlement commitment but instead takes places from within the existing humanitarian resettlement program. The Australian program charges sponsors exorbitant application fees, while simultaneously prioritizing refugees who are “job ready,” with English-language skills and ability to integrate quickly, undermining the principle of resettling the most vulnerable. As such, we argue that the CSP hijacks places from within Australia’s humanitarian program and represents a market-driven outsourcing and privatization of Australia’s refugee resettlement priorities and commitments.